THE CONSTRUCTION OF CORPORATE FAULT RELATED TO CORPORATE CRIMINAL ACTS IN THE NEW CRIMINAL CODE: IMPLICATIONS AND FORMULATIONS - Joice Soraya; Wahyu Prawesthi (Faculty of Law, Universitas Pekalongan, 2023)
In the development of modern criminal law, corporate crime has become a primary concern because corporations, as separate legal entities from the individuals within them, are increasingly involved in various widespread legal violations. Therefore, discussions regarding the construction of